Adjudicating a towers of hanoi contest - Wood, D. (International journal of computer mathematics, 1983)
The notion of a Towers of Hanoi contest is introduced and the complexity of some adjudication methods are investigated. We present linear time and space adjudication algorithms, that is optimal adjudication algorithms.